The Actual Use of Green Spaces by Children and Parents in Malang, Indonesia - Sri Een Hartatik; Akemi Itaya (Institut Pertanian Bogor (IPB University), 2018)
Green spaces in developing countries often are destroyed and degraded for other land uses. As increases in urbanization and population continue in Indonesia, it will be increasingly important to discuss green spaces around children. In this study, the actual use of urban green spaces by children were understood through questionnaires for children and their parents, and the strategy for increasing opportunity to use urban green spaces were discussed in Malang, a region of progressing urbanization in Indonesia. A total of 147 questionnaires were received from the children and 145 from their parents. While there were few green spaces around schools in Malang, especially in the center of the city, fortunately children liked to play in the outside more than other studies. However, children preferred to spend their time in well-maintained or level areas, such as parks and open fields. It might be important to provide parks with enough vegetation and attractive program within their living area in order to make them use green spaces. The cooperation with companies as CSR program for developing environmental education programs might be effective.